Analysis of Students Chemical Literacy through Ethnochemistry Learning in Material Colligative Properties of Solution - Bibit Harianto; Indarini Dwi Pursitasari; Leny Heliawati (UIN Fatmawati Sukarno Bengkulu, 2025)
The industrial revolution in the 21st century demands the creation of a generation that is responsive to change and has the competencies of Critical Thinking, Creative Thinking, Communication, and Collaboration (4C). The contextual learning process based on ethnochemistry is expected to increase students' motivation and interest in learning chemistry. Chemistry subjects that are classified as difficult and can be linked to local culture are the colligative properties of solutions. This study aims to analyze chemical literacy through learning with an Ethnochemical approach to the material of colligative properties of solutions. The research method used is quantitative descriptive research. Data collection using a test method, the test method is in the form of multiple-choice chemical literacy questions with a total of 10 validated questions and has a reliability index in the moderate category. The test method aims to determine students' chemical literacy in terms of content, context, and competence. The results of the study showed that the average chemical literacy of students in terms of content aspects was 49.2%; context aspects of 40.4%, and competency aspects of 50.6%. Th e average chemical literacy from these three aspects is categorized as “Not Enough”. The results of the study concluded that chemical literacy in ethnochemistry-based learning is in the “Not Enaough” category. The recommendation from this study is the need for innovation in chemistry learning through integration between ethnochemistry and STEM as well as the development of teaching materials in the form of ethnochemistry-based books that support the learning process.